A nationwide non-medical switch from originator infliximab to biosimilar CT-P13 in 802 patients with inflammatory arthritis: 1-year clinical outcomes from the DANBIO registry. Issue 8 (4th May 2017) - Glintborg, Bente; Sørensen, Inge Juul; Loft, Anne Gitte; Lindegaard, Hanne; Linauskas, Asta; Hendricks, Oliver; Hansen, Inger Marie Jensen; Jensen, Dorte Vendelbo; Manilo, Natalia; Espesen, Jakob; Klarlund, Mette; Grydehøj, Jolanta; et al.
Abstract : Objectives: According to guidelines, a nationwide non-medical switch from originator (INX, Remicade) to biosimilar infliximab (Remsima, CT-P13) was conducted in Danish patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (AxSpA). We investigated disease activity before/after switching and retention rates in the DANBIO registry. Methods: Disease activities 3 months before and after switch and changes over time were calculated. Flare was defined as change in 28 Joint Disease Activity Score (∆DAS28) ≥1.2 (RA/PsA) or Ankylosing Spondylitis Disease Activity Score (∆ASDAS) ≥1.3 (AxSpA). Crude and adjusted retention rates were compared with a historic cohort of INX-treated patients. Results: Eight hundred and two patients switched (403 RA/120 PsA/279 AxSpA; 51% women, age (median (IQR): 55 (44-66)) years). Follow-up was 413 (339–442) days. Prior INX treatment duration was 6.8 (4.3–9.5) years. Disease activities were similar 3 months before/after switch. Crude 1-year CT-P13 retention rate (84.1 (95% CI 81.3 to 86.5)) was similar to the historic IFX cohort (86.2 (95% CI 84.0 to 88.0), p=0.22). The adjusted absolute retention rates were 83.4 (95% CI 80.8 to 86.2) and 86.8% (95% CI 84.8 to 88.8), respectively (p=0.03). In total 132 patients withdrew (lack of effect: 71/132=54%, adverse events: 37/132=28%). Patients with previous INX treatment duration >5 years had longer CT-P13 retention. Conclusion: In 802 arthritis patients treated with INX for median >6 years, a nationwide non-medical switch to CT-P13 had no negative impact on disease activity. Adjusted 1-year CT-P13 retention rate was slightly lower than for INX in a historic cohort.